Cross-border cooperation across Polish borders: Thirty Years of cross-border Eldorado? - Jańczak, Jarosław (My University, 2021)
The article overviews cross-border cooperation across Polish borders in the last three decades. Deeply rooted in conflictive border legacies and border shifts in the first half of the twentieth century, they quickly became locations of symbolic reconciliation with neighbours and functional cooperation aiming at economic development. The non-linear character of these processes resulted from the changing political environment in the region.
Keywords: Polish borders; de-bordering; re-bordering; cross border cooperation